Czy zmierzamy w stronę autorytarnego sądowego procesu karnego? - Leżak, Kazimierz J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article discusses recent changes in the Polish Code of Criminal Procedure in the sphere of the prosecutor’s right to oppose decisions made by a court during the trial. The purpose of the article is to show the public prosecutor’s increasing interference in the course of criminal proceedings, which, as a result, makes it possible to take control over the course and outcome of specific criminal proceedings.
Keywords: autorytaryzm; postępowanie karne; władza sądownicza